General Need for Autonomy and Subjective Well-Being: A Meta-Analysis of Studies in the US and East Asia - Yu, Shi; Levesque-Bristol, Chantal; Maeda, Yukiko (Journal of happiness studies, 2018)
Self-determination theory proposes that human beings have universal basic psychological needs for autonomy, competence, and relatedness, which when satisfied lead to well-being. The current meta-analysis synthesized the correlations between the need for autonomy and subjective well-being. More specifically, because some researchers have questioned the role of autonomy in well-being in non-Western cultures, our meta-analysis focused on the results reported from studies conducted in the United States (US, a typical individualist culture) and East Asian countries (typical collectivist cultures). Random-effects analyses using 36 independent samples (22 from the US and 14 from East Asian samples including China and Japan) totaling 12,906 participants showed a moderate correlation ( r = .46, p < .001) between autonomy and subjective well-being. The difference between correlations for studies conducted in the East and West was not significant (Δ r = .05, p > .05). Overall, this study lends support to self-determination theory’s proposition that autonomy is a universal psychological need and provides suggestions for cultural practices and policies.